Analysis of the Meshing Transmission Characteristic of the Drilling Rig Rotary Table Bevel Gear based on the Virtual Prototyping Technology - Huang Anyi; Dai Yixiang; Hu Xushan; Tian Xiaozhu (Jixie chuandong)
The drilling rig rotary table bevel gear is an important transmission device for the drive drilling rig.A precise parametric rotary table bevel gear model is established in Pro/E.By means of the data conversion to the interface file parasolid,a virtual prototype model of spiral bevel gear meshing transmission is created in ADAMS.The meshing impact forces of the straight bevel gear are simulated under tow different working conditions.Through analysis,agood coincidence between simulation results and theoretical calculation of the date verified that the virtual prototype model of bevel gears parametric modeling is reasonable and correct.The method provides a theoretical reference for the further discussion of bevel gear transmission system.The accurate simulation result also provides a reasonable guiding for the optimization design of high-power domestic rig rotary table.